T1 mapping for diagnosis of mild chronic pancreatitis. Issue 4 (13th August 2016) - Tirkes, Temel; Lin, Chen; Fogel, Evan L.; Sherman, Stuart S.; Wang, Qiushi; Sandrasegaran, Kumaresan
Abstract : Purpose: To determine if the T 1 relaxation time of the pancreas can detect parenchymal changes in mild chronic pancreatitis (CP). Materials and Methods: This Institutional Review Board (IRB)‐approved, Health Insurance Portability and Accountability Act (HIPAA)‐compliant retrospective study analyzed 98 patients with suspected mild CP. Patients were grouped as normal ( n  = 53) or mild CP ( n  = 45) based on history, presenting symptomatology, and concordant findings on both the secretin‐enhanced magnetic resonance cholangiopancreatography (S‐MRCP) and endoscopic retrograde cholangiopancreatography (ERCP). T 1 maps were obtained in all patients using the same 3D gradient echo technique on the same 3T scanner. T 1 relaxation times, fat signal fraction (FSF), and anterior–posterior (AP) diameter were correlated with the clinical diagnosis of CP. Results: There was a significant difference ( P < 0.0001) in the T 1 relaxation times between the control (mean = 797 msec, 95% confidence interval [CI]: 730, 865) and mild CP group (mean = 1099 msec, 95% CI: 1032, 1166). A T 1 relaxation time threshold value of 900 msec was 80% sensitive (95% CI: 65, 90) and 69% specific (95% CI: 56, 82) for the diagnosis of mild CP (area under the curve [AUC]: 0.81). Multiple regression analysis showed that T 1 relaxation time was the only statistically significant variable correlating with the diagnosis of CP ( P < 0.0001). T 1 relaxation times showed a weak positive correlation with the pancreatic FSF (ρ = 0.33, P  = 0.01) in the control group, but not in the mild CP group. Conclusion: The T 1 relaxation time of the pancreatic parenchyma was significantly increased in patients with mild CP. Therefore, T 1 mapping might be used as a practical quantitative imaging technique for the evaluation of suspected mild CP. Level of Evidence: 3 J. Magn. Reson. Imaging 2017;45:1171–1176